Chromosome Analysis Protocols - Gosden, John R.; Gosden, John R. (Methods in Molecular Biology, 1994)
Chromosomes, as the genetic vehicles, provide the basic material for a large proportion of genetic investigations, from the construction of gene maps and models of chromosome organization, to the inves tigation of gene function and dysfunction. The study of chromosomes has developed in parallel with other aspects of molecular genetics, beginning with the first preparations of chromosomes from animal cells, through the development of banding techniques, which permitted the unequivocal identification of each chromosome in a karyotype, to the present analytical methods of molecular cytogenetics. Although some of these techniques have been in use for many years, and can be learned relatively easily, most published scientific reports—as a result of pressure on space from editors, and the response to that pressure by authors—contain little in the way of technical detail, and thus are rarely adequate for a researcher hoping to find all the necessary information to embark on a method from scratch. A new user needs not only a detailed description of the methods, but also some help with problem solving and sorting out the difficulties en countered in handling any biological system. This was the require ment to which the series Methods in Molecular Biology is addressed, and Chromosome Analysis Protocols forms a part of this series.